MANAJEMEN PERENCANAAN SARANA DAN PRASARANA PENDIDIKAN DI SDN 6 PADANG SIBUSUK - Sesmira, Meli; Marsena, Miftahul; Asmendri, Asmendri; Sary, Milya (Idaarah: Jurnal Manajemen Pendidikan, 2024)
In today's world. of learning, one of the factors that determines how to improve the quality of learning is how an institution manages the programming of existing tools and infrastructure. The existing tools and infrastructure can help teaching participants feel comfortable in the way they practice guiding. The research conducted uses a qualitative approach, where this research defines how the management of programming of facilities and infrastructure at State Lower School 6 Padang Sibusuk, Kupitan District, Sijunjung Regency, collects information through, question and answer, selection, programming management of existing tools and infrastructure including programming stages. the implementation and maintenance of records and maintenance has been going well by the school, the obstacles experienced by the lack of supporting budget for the provision of tools and infrastructure, on the other hand, make dealing with existing cases, the school principal always coordinates with the factors those given responsibility, request support from the school committee and also all parents of students who intend to overcome the problems to achieve the planned goals.